Senecavirus A in Pigs, United States, 2015 - Hause, Benjamin M.; Myers, O.; Duff, J.; Hesse, Richard A. (My University, 2017)
Senecavirus A (SVA) has been sporadically identified in pigs with idiopathic vesicular disease in the United States and Canada (1–3). Clinical symptoms observed include ruptured vesicles and erosions on the snout and lameness associated with broken vesicles along the coronary band. A recent report characterized SVA in pigs in Brazil with similar clinical symptoms in addition to a higher proportion of deaths than would be expected in pigs 1–4 days of age (4,5). Several outbreaks of this infection in pigs were reported in the summer of 2015 in the United States; the more severe clinical features resembled those seen in outbreaks in Brazil (6). Subsequent testing by PCR of 2,033 oral fluid samples from material submitted during 441 routine diagnostic testing procedures (from 25 states) identified 5 SVA-positive cases (1%) (7). Besides affecting animal health, SVA infection is notable because its clinical symptoms resemble those caused by foot-and-mouth disease and vesicular stomatitis viruses. When vesicular disease is observed in US swine, mandatory reporting and testing of animals for foreign animal diseases are required.
Citation: Hause, B. M., Myers, O., Duff, J., & Hesse, R. A. (2016). Senecavirus A in Pigs, United States, 2015. Emerging Infectious Diseases, 22(7), 1323-1325. doi:10.3201/eid2207.151951
Keywords: Idiopathic Vesicular Disease; Complete Genome; Immunology; Infectious Diseases